(3agQSJ GdfLGTj aj Yde GdQLGds - (3GdfLGTj, GdCSOj, CHh GdYHGS, , CMeO Hf Ydj Hf CMeO Hf GdYHGS, J (B450(3g`s ((3MGLj Hf SdWGf MSjf GdMSjfj GdWHSjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf (B... (3CeG HYO aEfj hbaJ Ydi eG PcQg GdSjO GdTQja (B... (3ef JYjjQ bhe ef eNGdajfG(B...s
(3BNQgG (B:s
(3dg cJGH GdRgO(B... (3bGd MOKfG CHh Ydj Hf geGe bGd MOKfG eMeO Hf LYaQ (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B172s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B196s
(3GdCYdGe(B: (3L(B1(3, U(B172s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B196s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs